Referral patterns after school medical examinations. Issue 6 (June 1989) - Rona, R J; Allsop, M; Morris, R; Morgan, M
Abstract : The incidence of sensory or language abnormalities and the factors influencing the clinical medical officers' decisions to refer children who failed developmental tests were studied. There were 1259 children examined and referrals for vision, hearing, and language assessment were made for 39(3.1%), 75(6.0%), and 27(2.1%), respectively. About 80% of these problems, however, were not known to the child health services when the children were 3.5 years old, mainly because children had moved to the district after the age of 3.5, and did not attend the 3.5 year screening clinics. Referrals formed only a small percentage of children who failed a test (11.0% failed vision, 19.5% hearing, and 24.6% language assessments). For vision and hearing the most important reason for the discrepancy was the clinical medical officers' wish to reassess children who failed the test before referring them. For the language test the clinical medical officer's often believed that the screening did not reflect the child's skills, which suggests that language screening as currently used in the district is not effective. Evaluation of the examination has highlighted the need to review the tests being used.